Effects of Dietary Hemp Seed and Flaxseed on Growth Performance, Meat Fatty Acid Compositions, Liver Tocopherol Concentration and Bone Strength of Cockerels - Skřivan, Miloš; Englmaierová, Michaela; Taubner, Tomáš; Skřivanová, Eva (Animals, 2020)
The aim of the study is to determine the effect of hemp seed (HS) of the nonpsychotropic variety Futura and extruded flaxseed (EF) in the diet of cockerels on cockerel growth performance, breast muscle and liver α- and γ-tocopherol concentrations, breast muscle fatty acid concentrations and tibia strength. Five hundred and forty one-day-old male Ross 308 cockerels are equally allocated into six groups. Each group has three replicates of 30 cockerels in pens with litter. The formulated diets are isoenergetic (the metabolisable energy ranged from 12.4 to 12.8 MJ/kg) and isonitrogenic (the protein concentration ranged from 209.7 to 210.9 g/kg) and provided ad libitum. During the experiment, which lasts 35 days, the control group is fed a diet without EF or HS. Rapeseed oil was the lipid source in the control diet. The diet for the second group contains EF at 60 g/kg, the diet for the third group contains HS at 40 g/kg, and the diets for the fourth to sixth groups contain HS and EF at 30 and 60 g/kg, 40 and 60 g/kg and 50 and 60 g/kg, respectively. At the end of the experiment, 15 cockerels of average weight are slaughtered per group, and the breast muscle, liver and tibia bone are dissected for chemical analyses. The all dietary combination of HS and EF increases (p < 0.001) cockerel body weight (2375-2493 g) more than HS alone (2174 g) or EF alone (2254 g). A similar finding is observed for the diet composition and tocopherol content in the liver, but the doses of HS required to achieve this effect are higher (40 and 50 g/kg). The tocopherol content in the breast muscle is not influenced by the diet. The dietary combination of 60 g/kg EF and 40 g/kg HS results in the most promising findings of the experiment, since it leads to the lowest n-6/n-3 polyunsaturated fatty acids ratio (p < 0.001; 1.75). Incorporation of HS into the diet increases cockerel tibia strength (p < 0.001), which is of great practical importance due to the frequent occurrence of limb fractures. To conclude, the dietary supplementation with 40 g/kg HS and 60 g/kg EF improves cockerel performance, meat and bone quality and deposition of α-tocopherol in the liver.
Keywords: broiler chickens; n-3 polyunsaturated fatty acid; breast muscle quality; vitamin E; tibia minerals